Malignant melanoma of breast: A unique case with diagnostic dilemmas - Jayasudha A. Vasudevan; Thara Somanathan; Anitha Mathews; Jayasree Kattoor (Wolters Kluwer Medknow Publications, 2014)
Melanomas arising in the skin, mucous membranes, and eye are encountered commonly than melanomas involving the breast. Melanomas in the breast are usually metastatic. Primary melanoma of the breast is extremely rare. We report a case of malignant melanoma of breast (primary/metastatic) that presented as a breast lump in a patient with no detectable cutaneous, mucosal or ocular lesion and who is a known case of squamous cell carcinoma of the oral cavity and had relapsed twice. The unexpected challenges faced during the diagnosis prompted us to report this case.